The Need for Ecohydrological Research in Brazilian Mountains: the Case of the Serra da Mantiqueira Range - Vilanova, Mateus Ricardo Nogueira [UNESP] (FapUNIFESP (SciELO), 2025)
Abstract While certain Brazilian ecosystems attract significant attention from the global scientific community, others - particularly those in mountainous regions, which are both unique and highly vulnerable - remain underexplored and inadequately understood, especially from the ecohydrological perspectives. This article calls for developing robust hydrological and ecohydrological research in the Brazilian mountains, which can contribute to their environmental protection and water resources management. To support this call, I present examples of the Serra da Mantiqueira Range, which is one of the most important Atlantic Forest biodiversity hotspots in the World, besides being an important water source for the Southeast Brazil. I do not intend to present an exhaustive approach to the hydrology/ecohydrology of Brazilian mountains, since this is not possible, given their complexity and heterogeneity. Therefore, I propose to debate and illustrate this theme, to point knowledge gaps, and to propose a research agenda to contribute to the understanding of the water/ecosystem interactions in Brazilian mountains.